Factors Associated with Adolescent Pregnancy in Selebar District Bengkulu City - Pitri Subani; Yuni Ramadhaniati; Rina Aprianti; Susilo Wulan (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Adolescent pregnancy is common public health problem around the world. It is associated with major reproductive health problems that are at risk complications and childbirth causes maternal death and unsafe abortion. Purpose this study was identify and analyzed factors associated adolescent pregnancy in District Selebar, Bengkulu City. It is an analytical survey research with a cross sectional approach. Population was all young women aded 15-19 years old. The number of samples is 105 people with Sampling technique used probability proportional to size method. The instrument used was a questionnaire. Data analysis in the form of univariate and bivariate using the Chi-Square (χ2) statistical test, the amount of risk using the calculation of the Odd Ratio (OR) with a 95% confidence interval. The Result showed 66% of respondents’last education was basic education, 59% of respondents' knowledge was in the low category, 70% of respondents 'parents' income was at low level, 57% of respondents were influenced by peers and the incidence of pregnancy was 55%. There is a significant relationship between education, knowledge, parents' income and peer influence on the incidence of adolescent pregnancy in Selebar District with OR 2.76; 2.98; 3,45 and 3 respectively. Conclusion that adolescent pregnancy is detrimental to the health of women is therefore a step to improve early age sex education, in order to they are open to knowledge about reproductive organs and more responsible in taking action. In addition to increasing public awareness in enforcing the marriage law, ensuring access to education for women.